Digital Marketing Training and Human Resource Management Motivation for Assisted MSMEs Calayan Educational Foundation, Inc. (CEFI, Philippines) Calamansi Juice - Tria Hatmanti, Lusia; Epsilandri Septyarini (IMPACTS: International Journal of Empowerment and Community Services, 2025)
Purpose This article aims to show how the implementation of digital marketing strategies and branding development can increase product visibility, strengthen competitiveness in the market, and optimize team efficiency through HR empowerment. In addition, this article provides a model that can be replicated by other MSMEs in an effort to achieve sustainable growth and long-term success. Methods The activities carried out were training and lectures on Branding and Digital Marketing as well as Human Resource Management Motivation in UMKM Assisted by Calayan Educational Foundation, Inc. (CEFI, Philippines) Calamansi Juice. The training materials were adjusted to the needs of UMKM in order to be able to answer various problems to improve entrepreneurial and promotional skills. Result and Disscusion Participants demonstrated a significant improvement in their understanding of digital marketing strategies, such as social media marketing, search engine optimization (SEO), and content creation. A workshop on branding enabled participants to design a cohesive brand identity, including logo creation and the development of a brand message that resonates with their target audience. The training also included HR capacity building, such as task delegation, effective communication, and motivation techniques, which have contributed to better team dynamics and productivity. Conclusion Key outcomes include improved understanding and application of digital marketing strategies, the development of a cohesive brand identity, and enhanced team dynamics through HR empowerment